(untitled) (Cadernos de Sociomuseologia, 2014)
This study aims to understand how the itinerancy was and is being used as an educational resource, particularly in museology, and how itinerant museums can respond to issues that arise in the face of new concepts and functions of the Museum, especially in its relationship with the community. Through the research on its history, through various projects of itinerant museums, we try to show the changes in the perception and application of this methodology. Keywords: Museums, Itinerancy, Community